DYNAMICS OF INDICATORS OF ORAL FLUID PROPERTIES IN CHILDREN WITH LESIONS OF THE ORAL MUCOSA AGAINST THE BACKGROUND OF ACUTE LYMPHOBLASTIC LEUKAEMIA DURING TREATMENT - Khotimska, Yu.V.; Kovach, I.V.; Lavrenyuk, Ya.V.; Buniatian, Kh.A.; Shnaider, S.A.; Yakimenko, D.O.; Shnaider, K.S. (World of Medicine and Biology, 2024)
The work was devoted to the study of the dynamics of indicators of the properties of oral fluid in children with lesions of the oral mucosa against the background of acute lymphoblastic leukemia during treatment with the methods developed by the authors. The clinical trials involved 126 children aged 2 to 18 years who were diagnosed with acute lymphoblastic leukemia. The most common inflammatory diseases of periodontal tissues and oral mucosa in children with acute lymphoblastic leukemia were chronic gingivitis and candidal stomatitis. All children who underwent clinical trials were divided into 2 groups – the main and comparison groups. Children in the comparison group were treated with standard protocol methods. Children in the main group were treated with the developed treatment and prevention complex. The obtained results of the studies showed a stimulating effect of the treatment and prevention measures on the correction of the properties of the oral fluid in both the main study and comparison groups.
Keywords: acute lymphoblastic leukaemia; chronic gingivitis; candidal stomatitis; oral mucosa; salivation rate; oral fluid viscosity; children